Pakistan’s fertilizer sector: Structure, policies, performance, and impacts - Ali, Mubarik; Ahmed, Faryal; Channa, Hira; Davies, Stephen (International Food Policy Research Institute, 2016)
The fertilizer industry in Pakistan, with US$3.74 billion per year in sales, now stands at a crossroads where, after an initial substantial contribution in boosting crop productivity, its future potential is being challenged. Fertilizer-responsive crop varieties, supplementary irrigation water, and a favorable policy environment in Pakistan have induced fast growth in fertilizer demand. On the supply side, the availability of gas at low prices along with a favorable investment environment resulted in the buildup of excessive manufacturing capacity. But recently, a shortage of gas and monopolistic behavior has led to underutilization and greater imports. Restrictive laws put fertilizer processing and marketing in a few hands, which has also affected its efficiency. Moreover, the yield response of fertilizer has tapered off and per hectare use is fast reaching its optimal level. The existing policy environment leads to higher costs, inefficient use, and a heavy burden on the government as it charges one-fourth of the market price for feedstock gas used in fertilizer manufacturing. In addition, the government imports urea and absorbs the difference in international and domestic prices.